A Combined Approach to Women's Health Is Associated With a Greater Likelihood of Repeat Mammography in a Population of Financially Disadvantaged Women - Karen Y. Gregory-Mercado, PhD, MPH; Julie Will, PhD, MPH; Susan True, MEd; Janet Royalty, MS; E. Thomas Starcher II; Olga Khavjou, MA; William Helsel, MS; William Kammerer; William Howe (Centers for Disease Control and Prevention, 2007)
IntroductionIntegrating one or more public health programs may improve the ability of programs to achieve common goals. Expanding knowledge on how program integration occurs, how it benefits each individual program, and how it contributes to the achievement of common goals is an important area of inquiry in public health.MethodsThe National Breast and Cervical Cancer Early Detection Program (NBCCEDP) and the Well-Integrated Screening and Evaluation for Women Across the Nation (WISEWOMAN) program combined data from 10 of their overlapping state or tribal programs to calculate prevalence estimates of repeat mammography at 18 months. The data were stratified by whether women attended the combined program or only the NBCCEDP. Logistic regression analyses were conducted to identify factors that were thought to independently contribute to a greater likelihood of a woman receiving a repeat mammogram.ResultsWomen who participated in both programs were 1.5 to 5.1 times as likely to be rescreened, depending on program location, as women who participated only in the NBCCEDP. WISEWOMAN participants who received a follow-up WISEWOMAN screening for chronic disease risk factors within a year of their initial WISEWOMAN screening were 5 times more likely to return for a follow-up mammogram through the NBCCEDP than were WISEWOMAN participants who did not.DiscussionParticipation in both the NBCCEDP and the WISEWOMAN program is associated with a greater likelihood of a woman returning for a follow-up mammogram within 18 months of her initial examination. Collecting more in-depth information on motivational factors and on the association between receipt of multiple services and a woman's engagement in a health program should be the subject of future research.